PERHITUNGAN BREAK EVEN POINT (BEP) PADA INDUSTRI RUMAH TANGGA CINCAU BUKIT ERNANI DI BUKIT BESAR – PALEMBANG - A, Reni Agustina; Sayuti, Jalaluddin; Dibyantoro, Dibyantoro (Jurnal Interprof, 2017)
The purpose of this research is to know break even point on rupiah and unit for product cincau hitam based to ascertain profit level and profit plan. In analyzing the problems, the writer used observation, interview, literature and using formula BEP. Based on the calculation, the break even point of cincau bukit ernani in rupiah is Rp 363.980.247,39 and in units are 97.061 kg and 24.265 tray. In 2016, Cincau Bukit Ernani want to plan to make a profit Rp 700.000.000,00. To achieve the budgeted profit Cincau Bukit Ernani must produce cincau hitam Rp 1.706.390.833 or 455.037 kg or 113.759 trays.